РАДІОХІРУРГІЧНЕ ЛІКУВАННЯ ХВОРИХ НА РЕЦИДИВНУ ГЛІОБЛАСТОМУ ТА ПРОГНОСТИЧНІ ФАКТОРИ, ЩО ВПЛИВАЮТЬ НА ЙОГО РЕЗУЛЬТАТИ - Glavatskyi, O.Ya.; Griazov, A.B; Chuvashova, O.Yu.; Kruchok, I.V.; Griazov, A.A.; Khmelnytskyi, H.V.; Shuba, I.M.; Stuley, V.A.; Zemskova, O.V. (PH Akademperiodyka, 2023)
Background: Glioblastoma (GBM) is the most prevalent malignant tumor of the brain in adults with the inherent aggressive behavior and high recurrence rate. The stereotactic radiosurgery (SRS) is currently considered as one of the effective modalities for GBM treatment allowing for the improvement of survival with the acceptable toxicity level. Aim: To assess the effects of various factors on the survival of GBM patients following SRS. Patients and Methods: We retrospectively reviewed treatment outcomes of 68 patients who received SRS for recurrent GBM treatment in 2014–2020. SRS was delivered with Trilogy linear accelerator (6 MeV). The area of recurrent tumor/continued tumor growth was irradiated. For the treatment of the primary GBM, the adjuvant radiotherapy was provided at the standard fractionated regimen with the total boost dose of 60 Gy divided to 30 fractions (Stupp’s protocol) in the setting of the concomitant chemotherapy with temozolomide. 36 patients then received temozolomide as the maintenance chemotherapy. SRS for the treatment of recurrent GBM was provided at a boost dose of 20.2 Gy on average being delivered into 1–5 fractions with average single dose of 12.4 Gy. The survival was analyzed by the Kaplan—Meier method with a log-rank test used for assessing the impact of the independent predictors on the survival risks. Results: The median overall survival (OS) was 21.7 months (95% confidence interval (CІ) 16.4–43.1), median survival after SRS was 9.3 months (95% CІ 5.6–22.7). The majority of patients (72%) were alive for at least 6 months following SRS and about half of patients (48%) survived for at least 24 months following the resection of the primary tumor. OS and survival after SRS depend significantly on the extent of the surgical resection of the primary tumor. The addition of temozolomide to radiotherapy prolongs survival in GBM patients. The relapse time affected significantly OS (p = 0.00008), but not survival after SRS. Neither OS, nor survival after SRS were affected significantly by such factors as the age of patients, the number of SRS fractions (one fraction vs several fractions), and target volume. Conclusion: Radiosurgery improves the survival in patients with recurrent GBM. The extent of the surgical resection and adjuvant alkylating chemotherapy of the primary tumor, overall biologically effective dose and time between the primary diagnosis and SRS affect significantly the survival. The search for the more effective schedules for treating such patients requires further studies with more numerous cohorts of patients and extended follow-up.